Infecção por Papilomavirus humano e Chlamydia trachomatis em amostras autocoletadas de mulheres de áreas rurais do Médio Solimões, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Sexually transmitted infections (STI) are serious public health problems in Brazil and worldwide. In addition to acute symptomatic infections, often quite uncomfortable and debilitating, infected people can remain silent reservoirs of the pathogen, generating serious long-term health problems (such as cervical cancer, sterility, hepatitis and others). Among STI, we highlight the Human Papillomavirus and Chlamydia trachomatis, as they are related to serious problems that can affect the female genital system, such as cervical cancer, Pelvic Inflammatory Disease, respectively. Riverside women, even geographically close to large centers, have difficulties in accessing health care because they live on the banks of rivers. For this reason, cervical-vaginal self-collection and molecular diagnosis by Polymerase Chain Reaction (PCR) have been studied to facilitate STI screening. In the city of Coari, health care is centralized in the urban area, with sporadic actions by professionals in the communities. This creates more difficulties in accessing disease diagnoses, treatment and health information. Thus, the present study aims to assess the prevalence of infection by Human Papillomavirus and Chlamydia trachomatis in riverside women in Coari City. A “house to house” approach was used to recruit women and the samples was obtained with COARI® brush (KOLPLAST®). DNA extraction was performed with the ReliaPrep ™ DNA (Promega©). The amplification of human genomic DNA, CT and HPV was done by PCR and the products were visualized by electrophoresis. Data tabulation was performed using Microsoft Excel ® 2013 and data analysis using Epi Info® software version 7.2 and SPSS® Inc. Version 22. The survey reached 58 communities across 6 micro-regions. The participants (n = 419) were between 18 and 70 years old, with a mean age of 34 (SD = 12). 84.8% were married or lived in a stable relationship with a partner. 56.1% had low education. 84.3% live on agriculture and 88.1% have a family income of up to 1 minimum wage. The age of the first sexual intercourse varied between 9 and 29 years (mean = 15.3; SD = 2.6). The average age of the first pregnancy was 16.2 years (SD = 4.4). The majority (83.1) reported having had between 1 and 5 partners in their lifetime. As for condom use, 62.4% reported not using it with their steady partner. 22.1% reported having had a miscarriage and 46.9% reported having had a pap smear in less than 1 year. 74.8% of women reported clinical complaints related to sexual health. The molecular results showed 100% positivity for human genomic DNA, the prevalence of CT was 1.1% (5/419) and HPV was 15.7% (66/419). It was also observed that the self-collection was accepted by 99.8% (n = 419) of the women interviewed. Therefore, the work contributed to the knowledge of the epidemiological situation in the region, creating the basis for implementing strategies for tracking the studied pathogens, and the possibility of expanding studies for other STIs.
Infection by Human Papillomavirus and Chlamydia trachomatis in self-collected samples of women from rural areas of the Middle Solimões, Amazon
Keywords: Doenças sexualmente transmissíveis; Saúde pública; Infecções sintomáticas agudas; Útero - Câncer; Comunidades ribeirinhas; CIÊNCIAS DA SAUDE; HPV; Chlamydia trachomatis; Epidemiologia; Zona Rural; Autocoleta